Բարդուղիմեոս Մարաղացու Տրամաբանության լատիներեն աղբյուրները. «Դիալեկտիկա» եւ “Summulae Logicales” - Տիգրան Սիրունյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассмотрены латинские источники логического трактата «Диалектика» униата Бартоломеоса Марагаци (XIV в.) и показано, что непосредственным источником всех его четырех частей являются одноименные трактаты I, IV, V, VII из труда “Summulae logicales” Педро Испанского. The article discusses the Latin sources of the logic of Uniate Bartholomew of Maragh entitled “Dialectics”, and through examples taken from the original source shows that the direct source of all four parts: Introduction, «Յաղագս հաւաքաբանութեան», «Յաղագս պատրանաց գրոցն», «Յաղագս տրամաբանական տեղեացն» treatises of the same name I, IV, V, VII: “De introductionibus”, “De sillogismis”, “De locis”, “De fallaciis” of “Summulae logicales” by Peter of Spain
Keywords: Literature